Differences in Fatty Acid Metabolism between MCDD and HFD Induced Metabolic Dysfunction-associated Fatty Liver Disease Model Mice - Jia-Xuan Wang; Xin-Zhu Liu; Zhen Guo; Hui-Lin Zhang; Li Qi; Jia Liu; Ping Liu; Guo-Xiang Xie; Xiao-Ning Wang (Biological Procedures Online)
Abstract Background The global incidence of metabolic dysfunction-associated fatty liver disease (MAFLD) is increasing annually, which has become a major public-health concern. MAFLD is typically associated with obesity, hyperlipemia, or metabolic syndrome. Dietary induction is one of the most common methods for preparing animal models of MAFLD. However, there are phenotypic differences between methionine-choline-deficient diet (MCDD) and high fat diet (HFD) models. Methods To explore the differences in hepatic fatty acid metabolism between MCDD and HFD induced MAFLD, we analyzed serum and liver tissue from the two MAFLD models. Results We found that liver fat accumulation and liver function damage were common pathological features in both MAFLD models. Furthermore, in the MCDD model, the expression of hepatic fatty acid transport proteins increased, while the expression of hepatic fatty acid efflux proteins and mRNA decreased, along with a decrease in blood lipid levels. In the HFD model, the expression of hepatic fatty acid uptake proteins, efflux proteins and efflux mRNA increased, along with an increase in blood lipid levels. Conclusion Impaired fatty acid oxidation and increased hepatic fatty acid uptake play key roles in the pathogenesis of the two MAFLD models. The inverse changes in de novo lipogenesis and fatty acid efflux may represent an important pathological mechanism that leads to the phenotypic differences between the MCDD and HFD models.